Taxonomic revision of the Amazonian species of Ropalomera Wiedemann, 1824 (Diptera: Ropalomeridae) - Kirst, Frederico Dutra; Ale-Rocha, Rosaly (Zootaxa, 2012)
A taxonomic revision of the Amazonian species of Ropalomera Wiedemann, 1824 (Diptera: Ropalomeridae) is presented,based on well-known and new morphological characters, especially of the male terminalia. Eight previously known spe-cies are redescribed, with illustrations: Ropalomera clavipes (Fabricius, 1805) (lectotype and paralectotypes here desig-nated), R. femorata (Fabricius, 1805), R. glabrata Prado, 1966, R. goyana Prado, 1966, R. nudipes Frey, 1959, R. tessellataPrado, 1966, R. tibialis Walker, 1852, and R. titillatrix Steyskal, 1967 (lectotype and paralectotypes here designated). Onenew species, R. albifaciata sp. nov., is described from the type-locality in Manaus, Amazonas, Brazil. The nine speciescan be identified with the dichotomous key provided. R. glabrata and R. goyana are reported for the first time for the stateof Amazonas, and the latter is also reported for the state of Pará. With this study, the number of known species in Amazonia is increased from six to nine.